2014
DOI: 10.1007/s11947-014-1402-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of Antioxidant Egg White Hydrolysates in a Continuous Stirred Tank Enzyme Reactor Coupled with Membrane Separation Unit

Abstract: The objective of this research was to design an efficient continuously operated membrane reactor with a separation unit for egg white protein (EWP) hydrolysis and production of hydrolysates with improved antioxidant properties. For this purpose, a mechanically stirred tank reactor coupled with the polyethersulfone ultrafiltration module with a molecular weight cutoff of 10 kDa was employed. Several proteolytic enzymes have been tested in order to obtain the best quality of peptide-based formulations intended f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
(56 reference statements)
2
8
0
Order By: Relevance
“…The activity of the hydrolysates against the DPPH radical was substantially lower than that shown in the inhibition of the ABTS radical, with TEAC values of µM of Trolox/mg vs. mM of Trolox/mg, respectively. These results are similar to those obtained in other works with enzymatic hydrolysates of egg white protein [ 37 , 42 , 60 ]. This difference is probably due to the distinct solubility and diffusion of the radicals used [ 62 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The activity of the hydrolysates against the DPPH radical was substantially lower than that shown in the inhibition of the ABTS radical, with TEAC values of µM of Trolox/mg vs. mM of Trolox/mg, respectively. These results are similar to those obtained in other works with enzymatic hydrolysates of egg white protein [ 37 , 42 , 60 ]. This difference is probably due to the distinct solubility and diffusion of the radicals used [ 62 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with several studies on egg white protein hydrolysates, where the degree of hydrolysis increased with hydrolysis time, using both enzymes of plant origin, such as papain [ 34 , 35 ], as well as digestive enzymes of animal origin [ 25 , 34 , 36 ], microbial origin (such as alcalase, neutrase, and thermolysin) [ 34 , 37 , 38 ], or fungal origin (Flavourzyme) [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…The reducing power was also positively correlated with the amounts of enzymes added but reached a maximal value of 0.66 at 12 U/mg. As the dose of the enzyme increased to 15 U, however, it showed an insignificant decrease because of the saturation of binding sites in the substrate [39]. ESM-EH exhibited higher Fe 2+ -chelating activity at low concentration of alkaline protease (3 U/mg), which is due to the reduction of disulfide bonds in the eggshell membrane to sulfhydryl groups.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in the results found by our research group (Sbroggio et al [8]), it was verified that the ABTS and DPPH free radicals scavenging ability and ferric reduction antioxidant power (FRAP assay) of protein hydrolysates of okara obtained by Alcalase increased significantly when the DH varied from 0 to 33.6%. Other authors also reported a positive effect of DH on antioxidant capacity [9,10] by increasing exposition of bioactive peptides. In addition, Lu et al [11] reported a gradual decrease in isoflavone glycosides, accompanied by an increase in aglycones, in the course of protein hydrolysis time.…”
Section: Introductionmentioning
confidence: 83%